The (endo)cannabinoid signaling in female reproduction: What are the latest advances?. (January 2020) - Cecconi, Sandra; Rapino, Cinzia; Di Nisio, Valentina; Rossi, Gianna; Maccarrone, Mauro
Abstract: Cannabis extracts like marijuana have the highest consumption rate worldwide. Yet, their societal acceptance as recreational and therapeutic drugs could represent a serious hazard to female human reproduction, because cannabis ingredients [termed (phyto)cannabinoids] can perturb an endogenous system of lipid signals known as endocannabinoids. Accumulated evidence on animal models and humans has demonstrated a crucial role of these endogenous signals on different aspects of female reproduction, where they act through an ensamble of proteins that synthesize, transport, degrade and traffic them. Several reports have recently evidenced the potential role of endocannabinoids as biomarkers of female infertility for disease treatment and prevention, as well as their possible epigenetic effects on pregnancy. The purpose of this review is to provide an update of data collected in the last decade on the effects of cannabinoids and endocannabinoids on female reproductive events, from development and maturation of follicles and oocytes, to fertilization, oviductal transport, implantation and labor. In this context, a particular attention has been devoted to the ovary and the production of fertilizable oocytes, because recent studies have addressed this hot topic with conflicting results among species.